Kualitas Audit Perusahaan LQ45: Moderasi Reputasi Auditor atas Pengaruh Fee, Tenure, dan Ukuran Perusahaan, 2020-2024 - Annisa Dwi Cahyani; Risanda Alirastra Budiantoro (Balance: Media Informasi Akuntansi dan Keuangan, 2026)
Audit quality is essential to ensure the reliability and credibility of corporate financial statements. This study aims to examine the effect of audit fees, audit tenure, and firm size on audit quality, with auditor reputation as a moderating variable. The research focuses on companies listed in the LQ45 index on the Indonesia Stock Exchange during 2020-2024. Using purposive sampling, 28 companies were selected, resulting in 140 observations. The study employs secondary data obtained from annual financial statements. Data analysis was conducted using panel data regression and Moderated Regression Analysis (MRA), with the Fixed Effect Model identified as the most appropriate model. The results indicate that audit fees, audit tenure, and firm size do not significantly affect audit quality. Auditor reputation is also unable to moderate the relationship between audit fees and audit tenure on audit quality. However, auditor reputation strengthens the relationship between firm size and audit quality, suggesting that larger firms tend to achieve higher audit quality when audited by reputable auditors. These findings highlight the importance of auditor reputation alongside independence and professional standards in determining audit quality.